Does Ethnoscience Based Problem Based Learning Model Improve Student’s Creative Thinking Skill in Chemistry Learning? Meta-analysis - Leny Christiana; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2024)
Many studies on ethnoscience-based problem-based learning models have an impact on students' thinking skills. The purpose of this study is to determine the effectiveness of ethnoscience-based problem-based learning to improve students' creative thinking skills in chemistry learning. This study used a meta-analysis method. Data in the study was obtained through the databases ERIC, Reseearcgate, ScienceDirect and google scholar. The criteria for data eligibility are 1) publications must be indexed by SINTA, Scopus and Google Scholar, 2) research related to ethnoscience-based problem-based learning models, 3) research published in 2018-2023, and 4) research must have complete data to calculate the value of effect size. Statistical analysis with the help of JASP application version 0.8.5. The results of the effect size analysis of the study with the random effect model showed a significant influence of ethnoscience-based problem-based learning models to improve students' creative thinking skills (z = 7,189; p < 0.001; 95% CI [0.816; 1.345]). Furthermore, the influence of ethnoscience-based problem-based learning models on creative thinking skills in strong criteria (rRE = 0.944). This research provides important information for applying ethnoscience-based problem-based learning models in schools